The Community Participation in Overcoming the Illegal Logging in Sangir Balai Janggo, Solok Selatan District, Indonesia - Lestari, Venny Wira Ayu; Lee, Aung Zin Kyaw (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Abstract The purpose of this study was to know the society’s perception in overcoming of illegal logging in South Solok district. This study was a qualitative study by using the key informant. Informants were selected with using purpose sampling technique. The techniques of data collection were observation, interviews, documentation and FGD (Focus Group Discussion). The effort that has been done by the government and society of south solok district in overcoming the illegal logging is establishing the unity of forest supervision based on area (PHBN), where the supervisory officers were recruited from the community leaders and youth. In conducting forest supervision, local government is always patrolling integrated and give the socialization to the community around the forest. Keyword: Participation, Forest logging